High nitrogen inhibits biomass and saponins accumulation in a medicinal plant Panax notoginseng - Zhu Cun; Hong-Min Wu; Jin-Yan Zhang; Sheng-Pu Shuang; Jie Hong; Tong-Xin An; Jun-Wen Chen (PeerJ, 2023)
Nitrogen (N) is an important macronutrient and is comprehensively involved in the synthesis of secondary metabolites. However, the interaction between N supply and crop yield and the accumulation of effective constituents in an N-sensitive medicinal plant Panax notoginseng (Burkill) F. H. Chen is not completely known. Morphological traits, N use and allocation, photosynthetic capacity and saponins accumulation were evaluated in two- and three-year-old P. notoginseng grown under different N regimes. The number and length of fibrous root, total root length and root volume were reduced with the increase of N supply. The accumulation of leaf and stem biomass (above-ground) were enhanced with increasing N supply, and LN-grown plants had the lowest root biomass. Above-ground biomass was closely correlated with N content, and the relationship between root biomass and N content was negatives in P. notoginseng (r = −0.92). N use efficiency-related parameters, NUE (N use efficiency, etc.), NC (N content in carboxylation system component) and Pn (the net photosynthetic rate) were reduced in HN-grown P. notoginseng. SLN (specific leaf N), Chl (chlorophyll), NL (N content in light capture component) increased with an increase in N application. Interestingly, root biomass was positively correlated with NUE, yield and Pn. Above-ground biomass was close negatively correlated with photosynthetic N use efficiency (PNUE). Saponins content was positively correlated with NUE and Pn. Additionally, HN improved the root yield of per plant compared with LN, but reduced the accumulation of saponins, and the lowest yield of saponins per unit area (35.71 kg·hm−2) was recorded in HN-grown plants. HN-grown medicinal plants could inhibit the accumulation of root biomass by reducing N use and photosynthetic capacity, and HN-induced decrease in the accumulation of saponins (C-containing metabolites) might be closely related to the decline in N efficiency and photosynthetic capacity. Overall, N excess reduces the yield of root and C-containing secondary metabolites (active ingredient) in N-sensitive medicinal species such as P. notoginseng.